Vibration performance of arch prestressed concrete truss girder under impulse excitation. (15th June 2018) - Cao, Liang; Liu, Jiepeng; Chen, Y. Frank
Highlights: Vibration of innovative APT girder is investigated experimentally and theoretically. Vibration of APT girder induced impulse incentive is exhibited. The investigated APT girder exhibits satisfactory vibration behavior. The analytical solution of APT girder subjected to impulse was obtained. Abstract: In this study, laboratory testing and theoretical analysis were carried out to investigate the human-induced vibration issues for a relatively new structural form, i.e. the arch prestressed concrete truss (APT) girder system. Ambient vibration was performed on the APT girder to capture its natural frequencies, damping ratios, and mode shapes. The APT girder system possesses high frequency and low damping. Heel-drop and jumping impact excited by a single person and dual persons were considered to evaluate the vibration performance and peak acceleration distributions for the APT girder system. The mid-span of the APT girder was selected as the key location for the vibration evaluation. It is found that the additional tester contributes to the acceleration attenuation. A reasonable shape function for the APT girder was proposed. The validity for the fundamental natural frequency was verified. The theoretical accelerations determined by the modal decomposition method with the proposed shape function agree generally well with the test results.